IMPLEMENTASI PRINSIP-PRINSIP GOOD GOVERNANCE DALAM MENINGKATKAN PELAYANAN PUBLIK : Studi Kasus di Kantor Kecamatan Karangan Kabupaten Trenggalek Jawa Timur - Yuliyanti, Fitria; Radjikan, Radjikan; Santoso, Teguh (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2022)
The government in organizing a country must surely pay attention to services. service itself is a form of communication between the government and the community. Service plays an important role in a government. In providing a service to the public, of course, it must consider several principles so that the services provided can be maximally accepted by the public. In an effort to organize maximum public services at the Karangan District Office, Trenggalek Regency, the principles of good governance must be applied. According to Andre Roudonuwu, Welson Rompas, and Jericho Pombengi, the principles of good governance include participation, transparency, responsiveness, justice, efficiency & effectiveness, and accountability. The purpose of this study is to determine the implementation of the principles of good governance in public services at the Karangan District Office and to find out the obstacles in applying the principles of good governance to public services at the Karangan District Office. The method in this research is descriptive qualitative by describing as clearly as possible the information in the research. From the results of the research, it is known that the implementation of the principles of good governance in improving public services at the Karangan District Office has been implemented. The principles of participation, justice, and accountability are more dominantly implemented than the principles of transparency and responsiveness which are not dominantly implemented